Hydrogen Sulfide Exposure to Public Health Risk Around Cibereum Landfill Area at Banjar City - arie ardiyanti rufaedah (JURNAL KESEHATAN LINGKUNGAN, 2019)
The process of spoilage of waste in the landfill produces air pollutant gases such as hydrogen sulfide (H2S) which was a colorless gas, highly flammable, and has a characteristic rotten egg odor. Communities around TPA who were continuously exposed to H2S gas has very at risk of experiencing health problems. The main entrance of H2S gas through the respiratory system so that it was quickly absorbed by the lungs rather than exposure through the mouth. This study aims to analyze the great health risks arising from exposure to hydrogen sulfide gas at the Cibeureum landfill in Banjar City. This research was a descriptive-analytic type with cross-sectional study design and it was analyzed with an environmental health risk assessment (EHRA) approach. The results of H2S concentration measurements were 0,004 ppm and still below the 0,02 ppm standard. Exposure projections indicate that people in the surrounding areas do not yet have non-carcinogenic risks (0,42â‰¤1). The safe duration of exposure is 24 years. If residents still live around the landfill for more than 24 years, it will endanger them and cause non-carcinogenic health risks. Complaints caused by civilians around the landfill consist of coughing, headaches, colds, shortness of breath, chest pain, and sore throat.